Sustainable Tourism : Theory and practice - Weaver, David B. (David Bruce) (Amsterdam ; London : Elsevier Butterworth-Heinemann, 2006)
Weaver discusses the challenges and concerns surrounding the issue of sustainable tourism and explores policies and strategies available for preserving, monitoring and prolonging sustainable tourism and ecotourism projects.
Includes bibliographical references (p. 209-226) and index.
Keywords: Ecotourism; Travel and Tourism